Perfil clínico-epidemiológico dos pacientes com epilepsia de difícil controle do Hospital Ophir Loyola (Belém-PA) - VIEIRA, Caroline Darold (2020)
Objective: identify the epidemiological profile of patients with refractory epilepsy as well as the predictors associated with this outcome. Methods: This case-control study searched the medical records of 83 epileptic patients following-up on Ophir Loyola Hospital, from May 2015 to March 2019. Qualitative variables were analyzed by Chi-squared test, meanwhile the quantitative variables were evaluated by the Mann-Whitney U test and Kruskal-Wallis post hoc Dunn test. Results: 55 patients had refractory epilepsy (66,2%) and 28 had well-controlled epilepsy (33,8%). The refractory group profile was composed predominantly by women (52,7%), from Belém (49,1%), with completed or uncompleted high school (32,7%), focal seizures (56,3%), more than 15 seizures in the first year of illness (47,3%) and without abnormalities in the last EEG (70,9%). The majority had an unknown cause for epilepsy (43,9%), but within the known causes there was a dominance of hippocampal sclerosis (20%). The means of age, treatment time latency, disease progression time, treatment time and seizures onset age were respectively: 34,1; 6,4; 19,5 and 15,1 years. The statistically significant predictors were: prolonged disease progression time, more than 15 seizures in the first year of illness, hippocampal sclerosis findings and provenance from Marajó. Conclusion: this analysis identified a patient’s profile in higher risk of developing refractory epilepsy, allowing earlier referral to specialists, as well as the application of prophylactic and alternative treatment methods.